2012
DOI: 10.1002/jmri.23788
|View full text |Cite
|
Sign up to set email alerts
|

1H‐MR spectroscopy and diffusion tensor imaging of normal‐appearing temporal white matter in patients with nasopharyngeal carcinoma after irradiation: Initial experience

Abstract: DTI and H(1)-MR spectroscopy can be used to detect early radiation-induced changes of temporal lobe NAWM following radiation therapy for NPC. Metabolic alterations and water diffusion characteristics of temporal lobe NAWM in patients with NPC after RT were dynamic and transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 39 publications
12
44
2
Order By: Relevance
“…In the post-RT-ED group, we have not found significantly changed cortical thickness in the temporal region, but previous DTI studies (Duan et al, 2016, Xiong et al, 2013) have detected abnormal temporal region in the post-RT-ED group. For example, using DTI method, Duan et al (2016) found higher mean diffusivity in the bilateral temporal regions in the post-RT-ED group than that of the pre-RT group.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In the post-RT-ED group, we have not found significantly changed cortical thickness in the temporal region, but previous DTI studies (Duan et al, 2016, Xiong et al, 2013) have detected abnormal temporal region in the post-RT-ED group. For example, using DTI method, Duan et al (2016) found higher mean diffusivity in the bilateral temporal regions in the post-RT-ED group than that of the pre-RT group.…”
Section: Discussioncontrasting
confidence: 93%
“…And CMBs in the temporal lobe is believed associating with increased likelihood of cognitive dysfunctions in NPC patients after RT (Shen, et al, 2015). Previous studies have found WM alterations in the temporal lobe in the earlier period after RT, including metabolic changes (Xiong, et al, 2013), and abnormalities of water diffusion (Chen, et al, 2015). Actually, brain abnormalities after RT may be multifocal and dispersed throughout GM within the treatment fields (Peterson, et al, 1995), especially in the temporal lobe (Chan, et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the FA values in the right parietal lobe WM markedly decreased in the post-RT 6-12 month group and the values in the right temporal lobe WM markedly decreased after 12 months, compared with that in the pre-RT group. In the late delayed reaction period, as the brain edema was absorbed, the degree of demyelination decreased, myelin regeneration occurred and the FA values in the partial lobe WM recovered gradually (7). In the present study, the FA values in the left parietal lobe and right cerebellar hemisphere WM did not markedly decrease after 6 months and the FA values in right parietal lobe WM did not decrease significantly after 12 months.…”
Section: Mni Coordinate (Mm) ------------------------------contrasting
confidence: 43%
“…Tract-based spatial statistics (TBSS) is a novel processing method of DTI data, with marked advantages compared with the manually drawn regions of interest (ROI) method (10). Previous studies have primarily used the ROI method and have been confined to the temporal lobe (6)(7). To the best of our knowledge, the present study was the first to examine the dynamic alterations in the microstructure of whole brain WM in distinct stages of NPC prior to and following RT, using the TBSS method.…”
Section: Introductionmentioning
confidence: 99%
“…A recent DTI study found that fractional anisotropy (FA) values showed significant change in different period, these abnormalities were most severe within 6 months after radiotherapy, and different brain regions exhibited distinct rates of recovery thereafter [14]. Furthermore, the indices of DTI have significantly changed in the temporal WM [15,16], as well as regions of normal-appearing WM beyond the target field. To date, for the small-world properties of brain structural networks in NPC patients, few studies focused on the difference between after radiotherapy group and before radiotherapy group.…”
Section: Introductionmentioning
confidence: 99%